Posttranslational Regulation of the NLR Family Pyrin Domain-Containing 3 Inflammasome - Shim, Do-Wan; Lee, Kwang-Ho (Frontiers in Immunology, 2018)
The NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome is a multi-protein complex that can be activated by a variety of pathogen-associated molecular patterns (PAMPs) or damage-associated molecular patterns (DAMPs). Inappropriate NLRP3 inflammasome activation can induce autoimmune or metabolic disorders. Therefore, NLRP3 is an attractive target against NLRP3 inflammasome activation, and specific targeting of NLRP3 might be an intriguing approach to the development of drugs for the treatment of NLRP3 inflammasome-related diseases. Although many studies with varied mechanistic approaches were reported in inhibition of NLRP3 inflammasome activation, mechanisms related to regulation of posttranslational modification (PTM) of NLRP3, as a focal point has not been thoroughly addressed. Recently, extensive investigations of PTMs of NLRP3 have led to partial understanding of the mechanisms involved in NLRP3 inflammasome activation. In this review, we focused on the role of PTMs regulating NLRP3 inflammasome activation.